New Energy Development and Issues in China during the 14th Five-Year Plan - Bibin HUANG; Yunzhou ZHANG; Caixia WANG (Zhongguo dianli)
New energy power generation is about to enter the era of grid parity. In the near and medium term, it will still develop rapidly. Its proportion in the total installed capacity of the whole power grid will continue to increase. With its position in the power system gradually changing, the development of new energy power generation should be considered in the development framework of the whole energy and power industry. Based on the trend of new energy generation cost and the power system operation cost caused by it, the grid parity and utilization parity in the future are analyzed in this paper. The new energy development in China during the 14th five-year plan and four key issues are studied. Finally, policy recommendations for realizing the coordinated development of high proportion new energy and power system are put forward.